Whole Brain Irradiation or Stereotactic RadioSurgery for five or more brain metastases (WHOBI-STER): A prospective comparative study of neurocognitive outcomes, level of autonomy in daily activities and quality of life. (January 2022) - Ferini, Gianluca; Viola, Anna; Valenti, Vito; Tripoli, Antonella; Molino, Laura; Marchese, Valentina Anna; Illari, Salvatore Ivan; Rita Borzì, Giuseppina; Prestifilippo, Angela; Umana, Giuseppe Emmanuele; Martorana, Emanuele; Mortellaro, Gianluca; et al.
Highlights: The main aim of MBM treatment is to palliate neurological symptoms and to maintain an adequate QoL. SRT could be the "new standard" over WBI in the management of MBM patients. Neurocognitive functions could deteriorate more after WBI than after SRT. Abstract: Aims: To evaluate neurocognitive performance, daily activity and quality of life (QoL), other than usual oncologic outcomes, among patients with brain metastasis ≥5 (MBM) from solid tumors treated with Stereotactic Brain Irradiation (SBI) or Whole Brain Irradiation (WBI). Methods: This multicentric randomized controlled trial will involve the enrollment of 100 patients (50 for each arm) with MBM ≥ 5, age ≥ 18 years, Karnofsky Performance Status (KPS) ≥ 70, life expectancy > 3 months, known primary tumor, with controlled or controllable extracranial disease, baseline Montreal Cognitive Assessment (MoCA) score ≥ 20/30, Barthel Activities of Daily Living score ≥ 90/100, to be submitted to SBI by LINAC with monoisocentric technique and non-coplanar arcs (experimental arm) or to WBI (control arm). The primary endpoints are neurocognitive performance, QoL and autonomy in daily-life activities variations, the first one assessed by MoCa Score and Hopkins Verbal Learning Test-Revised, the second one through the EORTC QLQ-C15-PAL and QLQ-BN-20 questionnaires, the third one through the Barthel Index, respectively. The secondary endpoints are time to intracranial failure, overall survival, retreatment rate, acute and late toxicities, changing of KPS. It will be considered significant a statistical difference of at least 30% between the two arms (statistical power of 80% with a significance level of 95%). Discussion: Several studies debate what is the decisive factor accountable for the development of neurocognitive decay among patients undergoing brain irradiation for MBM: radiation effect on clinically healthy brain tissue or intracranial tumor burden? The answer to this question may come from the recent technological advancement that allows, in a context of a significant time saving, improved patient comfort and minimizing radiation dose to off-target brain, a selective treatment of MBM simultaneously, otherwise attackable only by WBI. The achievement of a local control rate comparable to that obtained with WBI remains the fundamental prerequisite. Trial registration: NCT number: NCT04891471.